"Digging Deeper?": Insights From a Novice Researcher. (30th September 2020) - Wohlfart, Olivia
This article reflects on lessons learned from a qualitative research project. Due to my quantitative academic upbringing, I missed the opportunity to dig deeper into the qualitative research material. The article critically reflects the steps of constructing an interview guide, conducting interviews, performing a qualitative content analysis and interpreting the results. Ideas on overcoming these barriers are presented. The article concludes with a positive outlook in the form of recommendations for other novice researchers in qualitative research as well as an appeal to experienced researchers to accompany us on this path.